MyotonPro Is a Valid Device for Assessing Wrist Biomechanical Stiffness in Healthy Young Adults - Nguyen, Anh Phong; Detrembleur, Christine; Fisette, Paul; Selves, Clara; Mahaudens, Philippe (Frontiers in Sports and Active Living, 2022)
BACKGROUND: The MyotonPro is a portable device for measuring biomechanical and viscoelastic properties in superficial soft tissues. The aims of this study are firstly to validate the MyotonPro compared to a reliable gold-standard frame and secondly to observe the influence of MyotonPro measurement on the total wrist viscoelasticity. METHODS: Three silicone polymers with different elastic properties were assessed with the MyotonPro and with a reference rheometer (Universal Tribometer Mod). Then, a free oscillations method was used to measure the passive elastic and viscous stiffness of the wrist and compared to MyotonPro forearm measurements. RESULTS: A one-way ANOVA demonstrated the validity of the MyotonPro’s stiffness (p=0.001), decrement (p<0.001) and relaxation (p=0.008) parameters for measuring the elastic stiffness (k) of the three polymers. The MyotonPro parameters demonstrated excellent reliability on the forearm. Proximal and distal anterior myofascial measurements of the MyotonPro were moderately correlated to the elastic stiffness (p=0.0027‒0.0275, absolute r=from 0.270 to 0.375) of the wrist while the postero-distal myofascial tissues of the forearm demonstrated a moderate correlation with the viscous stiffness of the wrist (p=0.0096‒0.0433, absolute r=from 0.257 to 0.326). DISCUSSION: The MyotonPro is a valid device for measuring elastic stiffness as well as a portable, affordable and easy-to-use tool for quantifying the biomechanical properties and viscoelasticity of myofascial tissue in healthy subjects.